GPC characterization of emeraldine base in NMP containing ionic liquids - Yang, Dali; Fadeev, Andrei G.; Adams, Phillip N.; Mattes, Benjamin R. (Synthetic metals, 2007)
Strong aggregation between chains of polyaniline (PANI) emeraldine base (EB) molecules dissolved/dispersed in N-methyl-2-pyrrolidinone (NMP) results in a multi-modal molecular weight distribution in gel permeation chromatograph (GPC) results, regardless of how low the concentration of EB is. The addition of a salt, such as lithium chloride (LiCl), is known to improve EB solubility in NMP by deaggregating the polymer chains. However, we have found that ionic liquids, such as 1-methyl-3-butyl imidazolium tetrafluoroborate ([BMIM][BF 4]) or 1-methyl-3-ethyl imidazolium tetrafluoroborate ([EMIM][BF 4]), not only have less impact on the EB chain conformation than LiCl does, but also deaggregate the EB molecules more effectively. A mono-distributed GPC peak is obtained for EB ( M w up to 3 × 10 5 g/mol) dissolved in the NMP/ionic liquid solutions. Therefore, the EB molecular weight distribution is characterized more accurately by using the NMP/ionic liquid solution than the NMP/LiCl solution.